High-Intensity Resistance Training Does Not Produce Immediate Ultrasonographic Changes in Muscle Tendons. Issue 1 (11th January 2019) - Thygesen, Mathias Møller; Jordt, Ida; Kristensen, Malene Svane; Fisker, Filip Yang; Kildegaard, Sofie; Pfeiffer-Jensen, Mogens
Background: Chronic overload injuries to tendons can be visualized using ultrasonography, with characteristics such as tendon thickening and darkening. Purpose: To investigate whether these characteristics are evident in the patellar and Achilles tendons immediately after 1 session of high-intensity resistance training. Study Design: Controlled laboratory study. Methods: A total of 18 volunteers were randomized to an experimental group (n = 10) and a sham group (n = 8). The experimental group performed 5 circuits at maximum effort consisting of 5 weighted front squats, 10 box jumps (60/50 cm), and 15 double-under jump-rope jumps. The sham group performed a similar circuit consisting of 5 weighted shoulder presses, 10 push-ups, and 15 weighted biceps curls. Ultrasonograms were obtained before and after exercise, for a total of 30 minutes at intervals of 2.5 minutes for the first 10 minutes and 5 minutes for the remaining time. Tendon thickness and tendon matrix signals were measured. Statistics were performed using repeated-measures mixed analysis of variance (ANOVA). Results: Tendon thickness did not increase significantly over 30 minutes after both circuits. The mean grayscale value for the patellar and Achilles tendons increased for both the experimental and the sham groups. ANOVA showed that the experimental group was not a significant explanatory variable; however, the increased work of both groups was. A post hoc analysis found that the maximum increase in the tendon signal was a grayscale value of 10.8 for the patellar tendon (99.4% CI, 3.7-17.9; P = .002). Conclusion: This trial failed to reproduce an earlier study in which tendon thickness increased after high-intensity training. The tendons produced a hyperechoic signal after high-intensity resistance training, regardless of loading to the tendon. Chronic overload characteristics on ultrasonography were not evident immediately after acute loading of tendons. Clinical Relevance: There is a need for prognostic and diagnostic markers of tendinopathy especially because of the protracted course of subclinical development of an injury. This study assessed whether clinical findings for a chronic overload injury can be detected during acute overloading.